Recent developments in microbial oils production: a possible alternative to vegetable oils for biodiesel without competition with human food? - Christophe,Gwendoline (2012)
Since centuries vegetable oils are consumed as human food but it also finds applications in biodiesel production which is attracting more attention. But due to being in competition with food it could not be sustainable and leads the need to search for alternative. Nowdays microbes-derived oils (single cell oils) seem to be alternatives for biodiesel production due to their similar composition to that of vegetable oils. However, the cold flow properties of the biodiesel produced from microbial oils are unacceptable and have to be modified by an efficient transesterification. Glycerol which is by product of transesterification can be valorised into some more useful products so that it can also be utilised along with biodiesel to simplify the downstream processing. The review paper discusses about various potent microorganisms for biodiesel production, enzymes involved in the lipid accumulation, lipid quantification methods, catalysts used in transesterification (including enzymatic catalyst) and valorisation of glycerol.